The postictal state — What do we know?. (12th May 2020) - Pottkämper, Julia C. M.; Hofmeijer, Jeannette; van Waarde, Jeroen A.; van Putten, Michel J. A. M.
Abstract: This narrative review provides a broad and comprehensive overview of the most important discoveries on the postictal state over the past decades as well as recent developments. After a description and definition of the postictal state, we discuss postictal sypmtoms, their clinical manifestations, and related findings. Moreover, pathophysiological advances are reviewed, followed by current treatment options.